Internal migration drivers and patterns a case study of Cagayan De Oro City - Mejia, Katherine Coronado; Chaves,Carmeli Marie C.; Napalang, Ma. Sheilah G.; Nguyen Xuan Thinh (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
According with the Census of Population and Housing of Philippines 2010, the number of internal migrants between 2005 and 2010 was 2.9 million of persons, which have moved towards to the major urban centers of the country, such as Metro Manila, Cebu and Davao, but also this pattern of migration has influenced the growth of medium and small towns, and peri-urban areas. Migration as well as the development and growth of urban settlements need to be managed and planned, to make use of the full potential of migration for the development. However and effective management of internal migration needs proper and relevant statistical data. Adequate information and data will allow a better understanding of the internal migration dynamics and needs of the migrants, and thereby for the design of appropriate strategies and policies.In the Philippines some researchers and studies on internal migration have been conducted and published in the between the seventies and nineties, which took as a method of study the circulation of the Net Migration Rate and the analysis of Information obtained by the censuses. Although these studies are important contributions to the historic analysis of the patterns of migration within the Philippines, they are already dated and they neglected to study the determinants of migration, why individuals and families decide to leave their current residence anbd start a new live elsewhere. There i a need to address the current gap on information about the mobilization of people inside of the country. Therefore this study was designed to analyze the dynamics of these movements within the Philippine territory. The principal objective of this research is to identify the drivers and patterns of the internal migration, and to define the socio demographic characteristics of the migrants, by studying the case of the emerging city of Cagayan de Oro in Mindanao. To accomplish the objective of this research, an exploratory study methodology was conducted. A hybrid model of data collection, both qualitative and quantitative, was implemented. Firstly, a review of literature was held to identify the historic patterns of movements and migratory streams within the territory of Philippines, as well seven (7) semi-structured interviews to experts were undertaken. Secondly a survey was designed and conducted to 390 households in Cagayan de Oro with the aim to characterize the internal migrants and to identify their patterns of migration and the reason for each movement. As a result of this research, it was possible to observe that historically in the Philippines there has been an increasing trend of human mobilizations towards large urban or peri-urban centers of the country, especially since seventies. Theses movements were mostly of young population in the working age, and with an important female participation. Similar results were obtained in the analysis of the migratory dynamics in the city of Cagayan de Oro, more than one thousand of movements recorded from 1951 to 2016,especially within the Northern Mindanao Region. The migration patterns identified were mainly Rural-Urban and, in recent decades, Urban-Urban, associated principally to economic drivers (job search and livelihood alternatives) together with social drivers (family networks and the change of marital status). However, it was also identified a growth of movements from urban centers to rural areas, linked to the desire of the migrants, mostly women, to return home.
Thesis (M.S. Regional Development Planning)--University of the Philippines Diliman
Keywords: Migration,Internal -- Philippines -- Cagayan De Oro City; Rural-urban migration -- Philippines -- Cagayan De Oro City; Migrant labor -- Philippines -- Cagayan De Oro City